2015
DOI: 10.4103/0253-7613.161275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Nerium indicum by inhibition of prostaglandin E2 in murine splenic lymphocytes

Abstract: Objective:Nerium indicum Mill (syn. N. oleander L. and N. odorum Aiton; family: Apocynaceae) is a medicinal plant, used in the treatment of diverse ailments including various chronic inflammatory diseases in traditional medicine. We have previously demonstrated the immunomodulatory activity of a bioactive fraction of Nerium indicum leaf (NILE) by studying up-regulation of interleukin-2 (IL-2), IL-10, interferon-gamma and down regulation of IL-4, tumor necrosis factor-alpha (TNF-α), nitric oxide, cyclooxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a preliminary study, Erdemoglu et al [50] demonstrated anti-inflammatory activities of ethanolic and aqueous extracts of oleander leaves. Moreover, the 70 % hydro-methanolic extract of oleander leaves were demonstrated to possess anti-inflammatory activities by modulation of Th1/Th2 cytokine levels accompanied by inhibition of NO, COX and PGE 2 levels in concanavalin A activated murine splenic lymphocytes [15, 16]. In the present study, CCl 4 toxicity resulted significant ( p  < 0.001) increase in TNF-α and NO levels, which were subsequently lowered by the oleander extracts.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In a preliminary study, Erdemoglu et al [50] demonstrated anti-inflammatory activities of ethanolic and aqueous extracts of oleander leaves. Moreover, the 70 % hydro-methanolic extract of oleander leaves were demonstrated to possess anti-inflammatory activities by modulation of Th1/Th2 cytokine levels accompanied by inhibition of NO, COX and PGE 2 levels in concanavalin A activated murine splenic lymphocytes [15, 16]. In the present study, CCl 4 toxicity resulted significant ( p  < 0.001) increase in TNF-α and NO levels, which were subsequently lowered by the oleander extracts.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, another recent study showed that N. indicum leaf extract attenuates CCl 4 mediated hepatotoxicity in Swiss albino mouse [14]. Simultaneously, the same 70 % hydro-methanolic extract of oleander leaf possess anti-inflammatory activities by modulation of Th1/Th2 cytokine balance, inhibition of cyclooxygenase, prostaglandin E 2 (PGE 2 ) and nitric oxide levels in mitogen induced splenic lymphocytes [15, 16]. Moreover, diverse pharmacognostic activities such as anti-diabetic, anti-microbial, antinociceptive, neuroprotective, anti-ulcer, anti-cancer etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dey P et al have demonstrated that Nerium Indicum (Karaveera) has demonstrated potent anti-inflammatory activity by inhibiting PGE2 expression in murine lymphocytes. This is possibly due to the suppression of NO, TNF-, and COX activity and an increase in IL-10 levels, as well as immunomodulatory activity by up-regulating IL-2, IFN-, and IL-10 expression and down-regulating IL-4, TNF-, in vitro [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%